Conditions Of Fuel Filling Dispenser Trouble – Free Operation (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Regularly on the filling stations (FS) there are failures at priming of transport vehicles, when a driver, driving away after priming, forgets to smuggle out of a pistol from the mouth of filling tank of car. Thus, at wedging of pistol in the tank of car, there are not only breaks in a chart a pistol is a hose but also serious destructions of fuel filling dispenser (FFD). In the present paper the mathematical model of functioning of chart is considered vehicle - fuel filling dispenser. From the analysis of the got model, if a car begins motion with the undrawn pistol out of a fuel tank, the geometrical parameters of chart are determined vehicle - fuel filling dispenser, at which slipping out of pistol or his wedging will be in the mouth of tank which possible consequences are considered for (tearing away of pistol from a hose, tearing away of hose from corps of filling vehicle, break of hose, deformation of fuel filling dispenser). The geometrical parameters of chart are determined fuel filling dispenser, at which "forgetfulness" of driver will not result in damages of fuel filling dispenser f, and there will be slipping out of pistol from the mouth of fuel tank of car.